2020
DOI: 10.1002/14651858.cd013203.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Induction immunosuppression in adults undergoing liver transplantation: a network meta-analysis

Abstract: Induction immunosuppression in adults undergoing liver transplantation: a network meta-analysis (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 122 publications
0
10
0
Order By: Relevance
“…36 Our findings are consistent with the previous Cochrane review of effectiveness of rATG on preventing AR among recipients with rATG compared with those with basiliximab. 38 We further observed that the effect did not differ among older (≥65 y) and younger (18-64) recipients.…”
Section: Discussionmentioning
confidence: 55%
“…36 Our findings are consistent with the previous Cochrane review of effectiveness of rATG on preventing AR among recipients with rATG compared with those with basiliximab. 38 We further observed that the effect did not differ among older (≥65 y) and younger (18-64) recipients.…”
Section: Discussionmentioning
confidence: 55%
“…Data on patient outcomes related to induction IS choice are lacking. The previously cited low-quality data does not show significant differences in outcomes based on induction regimen (2,3).…”
Section: Discussionmentioning
confidence: 77%
“…The overall clinical impact of this variation in pediatric practice is unknown. In adults, previous systematic reviews have found minimal differences between T-cell depleting antibody (TDA) induction and non-TDA with many limitations based on low-quality evidence (2,3). Regarding the impact of costs on clinical outcomes, a 2016 examination of differences in utilization among pediatric liver transplant centers concluded that there was no correlation between higher overall costs and mortality, graft failure, or lower rates of readmission (4).…”
mentioning
confidence: 99%
“…The network meta-analysis is mainly used to compare the clinical efficacy of three or more interventions 9 . In this study, four types of combined Chinese medicine with azithromycin for treatment of MPC were analyzed.…”
Section: Discussionmentioning
confidence: 99%